Study on vertical vibration control of long-span steel footbridge with tuned mass dampers under pedestrian excitation. (March 2019) - Wang, Dayang; Wu, Chengqing; Zhang, Yongshan; Li, Shangwei
Abstract: This paper aims to study crowd-induced vibration control of long-span steel footbridges with different dynamic characteristics by combining methods of site measurement and numerical simulation. Four kinds of footbridge models with sensitive vertical natural frequencies of easily generating human-bridge resonance under pedestrian loading are designed based on an actual steel footbridge. The numerical models are firstly validated by comparative investigation between the site measurement and the simulation. Detailed study on dynamic responses of the four footbridges with and without controlling systems of tuned mass damper (TMD) and multiple tuned mass damper (MTMD) is then conducted under 13 cases of crowd random excitations, rhythmic running and jumping excitations. Results show that the numerical simulation agrees well with the site measurement data. TMD system is found to be highly efficient in reducing vibration responses only when the excitation frequency is basically consistent with the structural natural frequency, which obviously limits the application of TMD system in footbridges as wider excitation frequency bandwidth is caused by human activities. MTMD system are demonstrated to be with higher vibration absorption robustness appearing predominant and stable capacity of reducing structural vibrations under all the crowd random and rhythmic excitations for the four footbridges. Highlights: Vertical vibration control of long-span footbridges with different dynamic characteristics is investigated by site measurement and numerical simulation. Crowd excitations, such as random crowd, rhythmic running and jumping crowd, are discussed to show dynamic responses and controlling effectiveness of TMDs. TMD system is found to be highly efficient in reducing vibration responses only when the excitation frequency is basically consistent with the structural natural frequency. MTMD system are demonstrated to be with higher vibration absorption robustness appearing predominant and stable capacity of reducing structural vibrations under the crowd random and rhythmic excitations.